The Influence of Islamic Work Ethic, Spiritual Suggestion, and Work Environment on Employee Performance at Bumdes with the Mediation of Device Synergy at Bumdes Nawamitra Mandiri, Purbalingga Regency - Huda, Fatkhilil (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
This research is a survey research on BUMDES Employees in Pengadegan District, Purbalingga Regency. This research is entitled